Dissociating central and auditory attention: Is there a shared bottleneck for response selection and auditory search? - Kattner, Florian; Reimer, Christina B (Quarterly Journal of Experimental Psychology, 2020)
Central and auditory attention are limited in capacity. In dual-tasks, central attention is required to select the appropriate response, but because central attention is limited in capacity, response selection can only be carried out for one task at a time. In auditory search tasks, search time to detect the target sound increases with the number of distractor sounds added to the auditory scene (set sizes), indicating that auditory attention is limited in capacity. Here, we investigated whether central and auditory attention relied on common or distinct capacity limitations using a dual-task paradigm. In two experiments, participants completed a visual choice discrimination task (task 1) together with an auditory search task (task 2), and the two tasks were separated by an experimentally modulated stimulus onset asynchrony (SOA). Analysing auditory search time as a function of SOA and set sizes (locus-of-slack method) revealed that the auditory search process in task 2 was performed after response selection in a visual two-choice discrimination task 1 (Experiment 1), but concurrently with response selection in a visual four-choice discrimination task 1 (Experiment 2). Hence, although response selection in the visual four-choice discrimination task demanded more central attention as compared with response selection in the two-choice discrimination task, the auditory search process was performed in parallel. Distribution analyses of inter-response time further indicated that parallel processing of response selection and auditory search was not influenced by response grouping. Taken together, the two experiments provided evidence that central and auditory attention relied on distinct capacity limitations.